(untitled) (قضايا سياسية, 2022)
The year 2003 witnessed remarkable developments in the issue of dealing and protection through effort. To guarantee the rights and freedoms of their members in the 2005 constitution, but there are negative images that reduced the effectiveness of these arrangements, and it is clear that members of minorities lack many means of protection, which was the most dangerous turning point in 2014. ... and what the terrorist organizations left in large areas. from Iraq. Most of them were areas where minorities were concentrated, such as Nineveh, Diyala and Salah al-Din, and today, after the defeat of the terrorist organizations (ISIS), members of minorities still lack the means of protection that would reconnect them with The social system that needs to implement the means, mechanisms and arrangements to advance these facts. Minorities because they are an integral part of the Iraqi social fabric.